Preparation of a Cenosphere Curing Agent and Its Application to Foam Concrete - Zhongwei Liu; Kang Zhao; Yufei Tang; Chi Hu (Advances in Materials Science and Engineering)
Cenospheres are hollow and spherical particles extracted from fly ash. Controllable separation of cenosphere particles with different densities and sizes can be realized by controlling the density of a flotation solution of cenospheres. In this paper, cenospheres were corroded by hydrofluoric acid to produce perforated pores on their shell surfaces. Then, the cenospheres were mixed with water to prepare the cenosphere curing agent. Foam concrete was prepared using ordinary Portland cement (42.5 R), vegetable protein foaming agent, fly ash, cenospheres, and the cenosphere curing agent as raw materials. The water absorption rate of the cenosphere curing agent was 156.0 wt.%, and 85% of the loaded water was released at a relative humidity of 97.4%, which met the microenvironment requirements of foam concrete. Addition of the cenosphere curing agent during foam concrete preparation has the following positive functions for foam concrete: inhibiting autogenous shrinkage, promoting the hydration degree, improving the state of the interfacial transition zone between cenospheres and the hardened cement paste, reducing the number of connected pores, relieving the stress concentration on the pore walls, and enhancing the compression strength of the foam concrete.